NALAR IJTIHAD JILBAB DALAM PANDANGAN M. QURAISH SHIHAB (Kajian Metodologi) - Wartini, Atik (Sunan Kalijaga State Islamic University & The Asia Foundation, 2014)
Discussion of the jilbab is truly very interesting. In several past studies, the concept of wearing the jilbab hasÂ been seen as very controversial. There have been several contemporary Islamic scholars (ulama) with interesting perspectives on the jilbab. One of these Indonesian scholars is the Islamic interpretor (Mufassir) M. Quraish Shihab, who has written a book on the jilbab. Although the jilbab is not the area of concern of the author, using prior knowledge I will look at M. Quraishâ€™s rationale in making the controversial decision to write on the jilbab and also at his research methodology. It is his research methodology on law-making that the author particularly focuses on in this paper.